Nicotiana benthamiana asparagine synthetase associates with IP‐L and confers resistance against tobacco mosaic virus via the asparagine‐induced salicylic acid signalling pathway. (6th October 2021) - Liu, Changyun; Tian, Shaorui; Lv, Xing; Pu, Yundan; Peng, Haoran; Fan, Guangjin; Ma, Xiaozhou; Ma, Lisong; Sun, Xianchao
Abstract: Asparagine synthetase is a key enzyme that catalyses the conversion of amide groups from glutamine or ammonium to aspartate, which leads to the generation of asparagine. However, the role of asparagine synthetase in plant immunity remains largely unknown. Here, we identified a Nicotiana benthamiana asparagine synthetase B (NbAS‐B) that associates with tomato mosaic virus coat protein‐interacting protein L (IP‐L) using the yeast two‐hybrid assay and examined its role in tobacco mosaic virus (TMV) resistance. The association of IP‐L with NbAS‐B was further confirmed by in vivo co‐immunoprecipitation, luciferase complementation imaging, and bimolecular fluorescence complementation assays. IP‐L and NbAS‐B interact in the nucleus and cytosol and IP‐L apparently stabilizes NbAS‐B, thus enhancing its accumulation. The expressions of IP‐L and NbAS‐B are continuously induced on TMV‐green fluorescent protein (GFP) infection. Co‐silencing of IP‐L and NbAS‐B facilitates TMV‐GFP infection. Overexpression of NbAS‐B in tobacco reduces TMV‐GFP infection by significantly improving the synthesis of asparagine. Furthermore, the external application of asparagine significantly inhibits the infection of TMV‐GFP by activating the salicylic acid signalling pathway. These findings hold the potential for the future application of asparagine in the control of TMV. Abstract : Nicotiana benthamiana asparagine synthetase B (NbAS‐B) interacts with interacting protein L (IP‐L), facilitating the accumulation of NbAS‐B and increasing asparagine content, thus providing enhanced resistance to tobacco mosaic virus through the asparagine‐induced salicylic acid signalling pathway.